PENGARUH SUKU BUNGA LUAR NEGERI FEDERAL RESERVE (THE FED), NILAI TUKAR RUPIAH/US $ DAN INFLASI TERHADAP INDEKS HARGA SAHAM GABUNGAN DI BURSA EFEK INDONESIA PERIODE 2006-2008 - Misgayanti, .; Zuhroh, Idah (Jurnal Ekonomi Pembangunan, 2009)
The hypothesis are guess that Fed Rate negative influence to jakarta stock composite  index, guess that foreign exchange negative influence to jakarta stock composite  index and inflation negative influence to jakarta stock composite  index. Analysis instrument to knowing influence of fed rate, foreign exchange and inflation are use multiple linier regression analysis. To know what is the reach of independent variable influence to dependent variable use a hypothesis testing with a partial test (t test), simultant test (f test) and to knowing how the independent variable representative to dependent variable use a godness of fit (R2). The results of hypothesis analysis shows that Fed rate, foreign exchange and inflation have a simultant significant influence to jakarta stock composite  index. The evidence from the results shows that F test > F table (35,51624>2,95).  Partial test shows that Fed rate has negative influence to jakarta stock  composite index which t test > t table ((-6.016280 >2,048), foreign exchange has not influence to jakarta stock composite index with level a significant 5% and inflation has negative influence to jakarta stock composite index.